Documentary Film: A Very Short Introduction - Aufderheide, Patricia (New York Oxford University Press, 2007)
Documentary film can encompass anything from Robert Flaherty's pioneering ethnography Nanook of the North to Michael Moore's anti-Iraq War polemic Fahrenheit 9/11, from Dziga Vertov's artful Soviet propaganda piece Man with a Movie Camera to Luc Jacquet's heart-tugging wildlife epic March of the Penguins. In this concise, crisply written guide, Patricia Aufderheide takes readers along the diverse paths of documentary history and charts the lively, often fierce debates among filmmakers and scholars about the best ways to represent reality and to tell the truths worth telling.
Includes Index and Illustrations.
Keywords: Cine documental -- History Crítica